SEISMIC RISK ASSESSMENT OF LEVEES - Dario Rosidi (Civil Engineering Dimension, 2007)
A seismic risk assessment procedure for earth embankments and levees is presented. The procedure consists of three major elements: (1) probability of ground motion at the site, (2) probability of levee failure given a level of ground motion has occurred and (3) expected loss resulting from the failure. This paper discusses the first two elements of the risk assessment. The third element, which includes economic losses and human casualty, will not be presented herein. The ground motions for risk assessment are developed using a probabilistic seismic hazard analysis. A two-dimensional finite element analysis is performed to estimate the dynamic responses of levee, and the probability of levee failure is calculated using the levee fragility curve. The overall objective of the assessment is to develop an analytical tool for assessing the failure risk and the effectiveness of various levee strengthening alternatives for risk reduction. An example of the procedure, as it applies to a levee built along the perimeter of an island for flood protection and water storage, is presented. Variations in earthquake ground motion and soil and water conditions at the site are incorporated in the risk assessment. The effects of liquefaction in the foundation soils are also considered.